The burden on informal caregivers caring for a family member - Edit Valéria; Mária (Magyar Gerontológia, 2025)
Caring for geriatric patients is becoming an increasingly common phenomenon today. For caregivers, it represents a period characterized by many changes, which often place a burden on their lives.